Patient portals in German hospitals: Status quo and quo vadis - Ralf Plattfaut; André Coners; Jörg Becker; Carolin Vollenberg; Julian Koch; Marie Godefroid; David Halbach-Türscherl (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2020)
The health care sector in Germany has become increasingly important in the scientific field of information systems over the last decades. This development has been reinforced by the demographic change and, more recently, by the current Covid-19 pandemic. Irrespective of the field of work and application, digital interface processes, data acquisition, data exchange, as well as data preparation, analysis, and correct archiving are undoubtedly gaining in importance. They also enable new possibilities for service design and the corresponding provision of both digitized supply services and digitized information services. Against the background of increasing and more complex requirements in the health care system, digitalization can become a very important factor in the provision of services. This is especially true for hospitals. In hospitals, increasing data volume and level of detail increases the complexity of data documentation. Hospital staff currently spend a lot of time on data acquisition and transfer, and correspondingly less time is available for the beneficial core work with patients. Therefore, digitization and automation strategies through patient-oriented interactions are becoming increasingly necessary. Patient portals are one possible way to enable care and new services and to reduce the effort for comprehensive data collection. This paper presents the current situation in Germany regarding patient-oriented solutions by capturing, structuring, and analyzing the market of existing patient portals in German hospitals. Existing portal functionalities are identified and patient portals are evaluated against these functionalities. Our results show that there are only two patient portal solutions in the largest hospitals in Germany and that the existing portal solutions by far do not completely fulfill all functional categories. Based on these results, we develop and discuss further research questions for future research. This includes especially design-oriented research with regards to the digital patient journey.
Keywords: 650; Patient Portal; Portal; Portal function; Healthcare; Patient interaction; Digitalization; Patient Interface; Documentation effort